MENELITI AGAMA DENGAN MENGGUNAKAN MIXED METHODS - Rahmadi, Rahmadi (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2016)
Using mixed methods has not been widely discussed in the field of religious studies in Indonesia. This paper is presented to acomodate the use of this method in the study of religion in the region empirically. There are a number of strategies of mixed methods that can be used in studying religion, namely sequential mixed method, mixed method, and transformative concurrent mixed method. Each strategy is subdivided into several variants of strategies. All of these strategies can be used in studying the phenomenon of religion in accordance to the condition of the object, purpose of research and selection of researchers. Religious researchers can use this method if they want to understand religious phenomena simultaneously.